Brief school‐based interventions to assist adolescents' sleep‐onset latency: Comparing mindfulness and constructive worry versus controls. (13th February 2018) - Bartel, Kate; Huang, Chao; Maddock, Ben; Williamson, Paul; Gradisar, Michael
Summary: Difficulties falling asleep are common among adolescents, especially during times of stress. Adolescents may thus benefit from brief techniques (15 min) that decrease pre‐sleep cognitive‐emotional arousal and sleep‐onset latency. The present study used a 3 (intervention: mindfulness bodyscan mp3, constructive worry, control) by 3 (time: baseline, week 1, week 2) mixed‐model design on a school‐based sample of adolescents ( N = 232; M age = 15.9 ± 0.8 years, range = 14–18 years; 19% male), and a sub‐sample of adolescents with prolonged sleep‐onset latency (i.e. ≥30 min; N = 119; M age = 16.9 ± 0.9 years; 21% male). It was expected that the 15‐min pre‐recorded breath‐based mindfulness bodyscan, and constructive worry, would decrease sleep‐onset latency and pre‐sleep arousal similarly over time, relative to the control condition. A significant interaction was observed among adolescents with prolonged sleep‐onset latency, who completed ≥3 days for at least 1 week ( p = .001), where mindfulness decreased sleep‐onset latency relative to constructive worry and the control. Neither technique changed pre‐sleep worry or cognitive‐emotional arousal, or associated daytime functioning (both the whole sample and sub‐sample). A pre‐recorded mp3 breath‐based mindfulness bodyscan technique is a promising means by which adolescents with prolonged sleep‐onset latency can decrease sleep‐onset latency. This simple tool has potential for scalable dissemination by stakeholders (e.g. teachers), unqualified to treat adolescent sleep difficulties. Future studies are needed to determine whether benefits may extend to academic performance and mental health, if performed for a longer time period with increased compliance.